Shelf life estimation of ginisang burong bangus - Calong, Eileen Endaya; Francisco, Ma. Leonora dL. (2003., 2003)
ABSTRACT The study was conducted to estimate the shelf life of Ginisang Burong Bangus. Initial tests on commercial sterility were done to confirm the microbiological stability and sensory tests to determine the initial acceptability of the product. Based on the results of the first phase, the product was considered commercially sterile and moderately acceptable. In the second phase of the study, the product was stored at accelerated temperatures to determine the shelf life at these conditions. Sensory tests were utilized to determine the end of shelf life. Based on the results of chi-square, the product was perceived as significantly different on the 21st day at 35°C and 14th day at 45°C. Physico-chemical tests, such as pH, water activity, color, salt content, viscosity, were also conducted. Results showed that the product exhibited fluctuating values but with increasing or decreasing trend. Moreover, results showed that the product was likely to have a short shelf life. Microbiological tests were done to confirm the results of the sensory tests. However, based on the analyses, the product was still considered microbiologically stable with <10 CFU/g for Aerobic Plate Count, Yeast and Mold, and Lactic Acid Bacterial Count. The mode of deterioration was assumed therefore to be chemical. The final phase dealt with estimation of shelf life at 25°C. Q10 for the product was calculated using accelerated shelf life data obtained in the previous phase. Value of Q10 revealed that the product underwent oxidation reaction. This established value was used to determine shelf life at normal condition. Result of computation revealed that at 25°C, the product has a shelf life of only 31.5 da
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Fish -- Preservation; Fishery products